Creating digital history - case study: The Dorr Rebellion Project - Bailey, D. Russell (Infotheca - Journal for Digital Humanities, 2024)
Digital history, as a component of digital humanities, provides opportunities for scholars and students of history to create and contribute to the rapidly growing corpus of digital history research knowledge resources. This article describes and explicates an applied, non-theoretical, multifaceted, multimedia, fully-digital example of the creation of digital humanities by a small but broadly representative team of higher-education scholars and library staff (professional and support). The central topic and organizing principle is the 1842 North American Dorr Rebellion. The case study provides an adaptable model for other historical topics, other teams (higher-education or other researchers), including compelling reasons for this and other projects, the project’s organization and evolution, and both intended and incidental benefits from such collaborative projects. As an applied model, placement in, and specific connections to, the ongoing academic debate about the value of digital humanities and digital history versus the value of more traditional humanities and history is eschewed, rather emphasizing and focusing on practical guidance for collaborative creation of digital historical research knowledge resources.